2016
DOI: 10.1111/bjd.14399
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of selective JAK1 inhibitor GSK2586184 for the treatment of psoriasis in a randomized placebo-controlled phase IIa study

Abstract: Our study demonstrates that 12 weeks of treatment with GSK2586184 resulted in clinical improvement and was generally well tolerated in patients with moderate-to-severe plaque-type psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 22 publications
1
68
0
1
Order By: Relevance
“…There were no incidences of anaemia or thrombocytopenia during this study and the incidence of infections was low. Changes in lipid parameters were observed in this study, as has been reported in some studies with other JAK inhibitors . The most dramatic effects on HDL and LDL cholesterol were observed in subjects receiving PF‐04965842 BID.…”
Section: Discussionsupporting
confidence: 87%
“…There were no incidences of anaemia or thrombocytopenia during this study and the incidence of infections was low. Changes in lipid parameters were observed in this study, as has been reported in some studies with other JAK inhibitors . The most dramatic effects on HDL and LDL cholesterol were observed in subjects receiving PF‐04965842 BID.…”
Section: Discussionsupporting
confidence: 87%
“…Such clinical data may form an important foundation to support the evidence‐based care of psoriasis patients with itch symptoms. The following discussion reviews the itch effect of topical agents, systemics and biologics, and phototherapy, as revealed in recent studies (Table ) . Itch relief remains a significant gap in the treatment landscape for psoriasis, as not all patients are able to achieve control of this symptom, even with cleared or markedly improved skin.…”
Section: Management Of Itch In Psoriasismentioning
confidence: 99%
“…A new generation of JAK inhibitors, including both pan-JAK inhibitors (JAK1, JAK2, JAK3, and TYK2) and selective JAK inhibitors (i.e. JAK1 only or JAK3 only), are being developed 2,7178 . The advent of JAK inhibitors in dermatology has been met with significant excitement.…”
Section: Discussionmentioning
confidence: 99%